Pre-Analytical Factors Influence Vitamin D Measurement In Clinical Laboratory (International Journal of Scientific Research and Management (IJSRM), 2018)
It has been more than 90 years since the discovery of vitamin D and its capability to cure rickets in children. Recently, awareness is growing of the prevalence of vitamin D deficiency in the general population in association with an increased risk of several diseases. Analyses of vitamin D levels in blood samples provide direct measures of exposure to dietary or supplemented vitamin. This review is focused on the pre-analytical factors and challenges are known to affect the concentrations of vitamin D biomarkers. The pre-analytical measurement of disease relevant vitamin D deficiency in blood can vary as a function of differences in sample handling and processing. It could impact the accurate measurement of the diseases relevant vitamin D deficiency. Majority of the analysis in a clinical biochemistry laboratory requires serum or plasma as the analytical specimen and obtaining serum or plasma from a primary sample is an important step of pre-analytical procedure. Although vitamin D is considered as a relatively stable analyte, effect of pre-analytical conditions and stability of vitamin D in serum and plasma needs to be identified clearly.